A rare case of maxillary first molar with single root and single canal diagnosed using spiral computed tomographic scan - Ajay Saxena; Avantika Singh; Anuja Ikhar; Manoj Chandak (Wolters Kluwer Medknow Publications, 2014)
Variations in dental anatomy and canal morphology are found in all teeth. Knowledge of these variations, particularly the location and treatment of all canals, plays a key role in the success of endodontic therapy. The presence of extra canals, apical ramification, or lateral canals is commonly encountered, and their incidence and significance have been well-documented. However, the clinician should also be aware of the possibility of the existence of fewer root and/or canal numbers. Here is a case report of left maxillary first permanent molar with a single root and single canal. The goal of this clinical article is to report a maxillary molar with single root and single canal and to highlight the role of spiral computed tomography (SCT) as a method to confirm the three-dimensional (3D) anatomy of teeth.